Regional Development and Social Indicators in Croatia - Lovrinčević, Željko; Mikulić, Davor (Washington, DC, 2013)
This report, Regional Development and Social Indicators in Croatia, provides a comprehensive profile of social and economic characteristics of Croatia's regions as well as profiling the Government s social transfers to households. Demographic and economic structure of Croatian economy is analyzed, as well as the process of secondary distribution of income in Croatia on the regional level. According to data availability limitation, the analysis was restricted to the period 2001-2003. The report also assesses the effectiveness of government social transfers to households given the regional inequality profile. Sources of growth on the regional level and growth prospects were identified.